The use of a formula-based ketogenic diet in children with refractory epilepsy - Letícia Pereira de Brito Sampaio (Arquivos de Neuro-Psiquiatria)
ABSTRACT The ketogenic diet (KD) is a nonpharmacologic treatment that has been used for refractory epilepsy since 1921. The KD is a high-fat, low-carbohydrate, and restricted protein diet, which is calculated and weighed for each individual patient. Introducing and maintaining the diet for a long time remains a challenge. In this study, we evaluated the acceptability, tolerance, and efficacy of a formula-based KD in 10 children with refractory epilepsy. The ketogenic formula tested herein caused only mild KD-related adverse events and adequate adherence. Moreover, 60% of patients had more than 50% seizure frequency reduction and 10% were seizure-free.